Employer branding dimensions : A case study of how brands communicate their unique offering as an employer on social media - Ahokas, Ella (My University, 2022)
This research discusses the theme of employer branding and how its dimensions manifest themselves on social media. Employer branding is a marketing theme that hasn’t been in the spotlight for too long, is nowadays more important than ever as the business world is facing a current ‘war for talent’ and organizations struggle with attracting the best candidates. The objective of this research is to gain deeper understanding on employer branding and its central dimensions seen in social media. This way we can gain more knowledge on how brands seek to communicate their unique offering as an employer. This was approached with the following research questions 1. What are employer brand and employer branding? 2. What are the central dimensions of employer branding and 3. How do the central dimensions of employer branding manifest themselves in the researched companies’ social media channels? The theoretical framework of the research was built with the help of prior theoretical contributions and by combining them into an employer branding dimension framework. This framework included four dimensions: diversity, development value, work culture and social value. Later during the empirical study also CSR was added to the framework. The research topic is researched with the help of a qualitative social media content analysis that analyses two case companies – Accenture and Gofore. The research material was gathered from social media posts on LinkedIn and Instagram from the two companies’ accounts. According to the results, work culture, social value and diversity are the most important employer branding dimensions. The two case companies’ social media posts highlighted similar themes with each other and did not have any major differences between them. Regards to how the dimensions manifested themselves on social media the following four themes showed of great importance: focus on soft offerings, the importance of individuality and inclusivity, thought leadership content and the rise of CSR. All the three most important dimensions and the four themes can be seen to promote the ‘soft’ aspects of employer branding. These offer the employee intangible benefits and often something that is unique to the workplace. According to the results, organizations should focus on promoting these soft values, highlighting what actually makes their workplace unique and to present it as truthfully as possible.

Tämä tutkimus käsittelee työnantajabrändäystä ja sitä, miten sen eri ulottuvuudet näkyvät sosiaalisessa mediassa. Työnantajabrändäys on markkinoinnin teema, joka ei ole ollut valokeilassa vielä kovin pitkään, mutta on nykyään tärkeämpi kuin koskaan, kun yritysmaailma ja organisaatiot käyvät parhaillaan "sotaa kyvyistä" (war for talent) houkutellakseen parhaimpia työntekijöitä palvelukseensa. Tämän tutkimuksen tavoitteena on lisätä ymmärrystä työnantajabrändäyksestä ja sen keskeisistä ulottuvuuksista sosiaalisessa mediassa. Näin saamme lisää tietoa siitä, kuinka brändit pyrkivät viestimään työmarkkinoille ainutlaatuisesta tarjoamastaan työnantajana. Tätä teemaa lähestyttiin seuraavilla tutkimuskysymyksillä 1. Mitä ovat työnantajabrändi ja työnantajabrändäys? 2. Mitkä ovat työnantajabrändäyksen keskeiset ulottuvuudet ja 3. Miten työnantajabrändäyksen keskeiset ulottuvuudet näkyvät tutkittujen yritysten sosiaalisen median kanavissa? Tutkimuksen teoreettinen viitekehys rakennettiin aikaisempien teoreettisten kontribuutioiden avulla ja yhdistämällä ne työnantajabrändäyksen dimensioiden viitekehykseksi. Tämä viitekehys sisälsi neljä ulottuvuutta: monimuotoisuus, kehitysarvo, työkulttuuri ja sosiaalinen arvo. Myöhemmin empiirisen tutkimuksen aikana viitekehykseen lisättiin myös CSR-dimensio. Tutkimusaihetta tutkitaan laadullisen sosiaalisen median sisällönanalyysin avulla, joka analysoi kahta tapausyritystä – Accenturea ja Goforea. Tutkimusmateriaali on kerätty sosiaalisen median julkaisuista LinkedInissä ja Instagramissa kyseisten yritysten tileiltä. Tulosten mukaan työkulttuuri, sosiaalinen arvo ja monimuotoisuus ovat työnantajabrändäyksen tärkeimpiä ulottuvuuksia. Kahden tapausyrityksen sosiaalisen median julkaisut korostivat keskenään samanlaisia teemoja, eikä niissä ollut keskenään suuria eroja. Mitä tulee ulottuvuuksien ilmenemiseen sosiaalisessa mediassa, seuraavat neljä teemaa nousivat erityisen merkittävinä esiin: keskittyminen ’pehmeään’ tarjoamaan (soft offering), yksilöllisyyden ja inklusiivisuuden merkitys, ajatusjohtajuussisältö ja yhteiskuntavastuun (CSR) nousu. Kaikkien kolmen tärkeimmän ulottuvuuden ja neljän teeman voidaan nähdä edistävän työnantajabrändäyksen pehmeitä ominaisuuksia. Ne tarjoavat työntekijälle aineettomia etuja ja usein jotain työpaikalle ainutlaatuista. Tulosten mukaan organisaatioiden tulee keskittyä näiden pehmeiden arvojen edistämiseen, nostaa esiin mikä todella tekee heidän työpaikastaan ainutlaatuisen ja esitellä se mahdollisimman totuudenmukaisesti.
Keywords: employer branding, social media, employer branding dimensions, diversity, development value, social value, work culture